2014
DOI: 10.1111/1759-7714.12143
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Notch signaling pathway in cancer therapeutics

Abstract: Despite advances in surgery, imaging, chemotherapy, and radiotherapy, the poor overall cancer-related death rate remains unacceptable. Novel therapeutic strategies are desperately needed. Nowadays, targeted therapy has become the most promising therapy and a welcome asset to the cancer therapeutic arena. There is a large body of evidence demonstrating that the Notch signaling pathway is critically involved in the pathobiology of a variety of malignancies. In this review, we provide an overview of emerging data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 184 publications
2
25
0
Order By: Relevance
“…Notch expression is enhanced in the tubule cells of fibrotic kidneys from diabetic mice and humans and Notch interacting proteins have been identified that may be pertinent in normal and pathological functioning (21). The present study additionally demonstrated that HG activated the Notch pathway in a time-dependent manner in HKC cells and the maximum expression of Notch1 and NICD1 was observed at 24 h. HG increases Notch1 expression and releases NICD1, which travels into the nucleus and activates the downstream genes in HKC cells (22,23). DAPT, a Notch pathway inhibitor, suppresses activation of the Notch pathway by HG, which may inhibit γ-secretase-mediated proteolytic cleavage of Notch, reducing the release of the NICD from the plasma membrane into the nucleus (10).…”
Section: Discussionsupporting
confidence: 69%
“…Notch expression is enhanced in the tubule cells of fibrotic kidneys from diabetic mice and humans and Notch interacting proteins have been identified that may be pertinent in normal and pathological functioning (21). The present study additionally demonstrated that HG activated the Notch pathway in a time-dependent manner in HKC cells and the maximum expression of Notch1 and NICD1 was observed at 24 h. HG increases Notch1 expression and releases NICD1, which travels into the nucleus and activates the downstream genes in HKC cells (22,23). DAPT, a Notch pathway inhibitor, suppresses activation of the Notch pathway by HG, which may inhibit γ-secretase-mediated proteolytic cleavage of Notch, reducing the release of the NICD from the plasma membrane into the nucleus (10).…”
Section: Discussionsupporting
confidence: 69%
“…10,11 Although the role of different Notch transmembrane receptors in NSCLC development is not completely understood, Notch-1 is considered to play a vital role in cancer development [12][13][14][15] compared with other Notch transmembrane receptors. For instance, Notch-1 shows a growth-promoting function on NSCLC, whereas in SCLC, it plays a tumor-suppressive role.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Notch-1 shows a growth-promoting function on NSCLC, whereas in SCLC, it plays a tumor-suppressive role. 12 Baumgart et al 13 reported that Notch-1 expression from excessive ADAM17 activities leads to subsequent regulation of the epidermal growth factor receptor expression and tumorigenicity of NSCLC cells. Overexpression of Notch-1 has also been reported to inhibit apoptosis in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The r-secretase inhibitor of Notch pathway GSIs could prevent cleavage of r-secretase and keeping it to cell membrane thus inhibit Notch signal pathway. Inhibition of Notch signal pathway could inhibit cell proliferation and promote cell differentiation [18][19][20][21]. Besides, inhibition of Hedgehog signal pathway could also inhibit tumor effectively, having promised effect in clinic [22].…”
Section: Inhibition Of Self-renew Signal Pathwaymentioning
confidence: 99%
“…They plays very important role in CSCs maintenance as well. Notch pathway in endothelial cells significant promote the stemness of brain CSCs [18,20]. Developing the drugs targeting the micro-environment of CSCs will eliminate CSCs, the root of cancer.…”
Section: Cancer Micro-environmentmentioning
confidence: 99%